Kaupapa Māori Assessment: Reclaiming, Reframing and Realising Māori Ways of Knowing and Being Within Early Childhood Education Assessment Theory and Practice - Rameka, Lesley K. (Frontiers in Education, 2021)
The history of schooling for Māori has been one of cultural dislocation, deprivation and subjugation. Māori children were viewed as outside the norms of development suffering from ‘intellectual retardation’ which was attributed to disabilities related to acculturation. Traditional western assessment served to further these Eurocentric power ideologies that marginalise non-European peoples and cultures, such as Māori, as backward, inferior and deviant. Kaupapa (philosophical) Māori assessment can be viewed as an assessment approach that is derived from the Māori world, from a Māori epistemological perspective that assumes the normalcy of Māori values, understandings and behaviours. The validity and legitimacy of Māori language, cultural capital, values and knowledge are a given. Kaupapa Māori assessment works to challenge, critique and transform dominant educational perceptions of the Māori child, the nature of learning, pedagogy and culturally valued learning. This article explores ways that kaupapa Māori assessment builds upon Māori philosophical and epistemological understandings to express Māori understandings of knowledge, knowers and knowings, in order to reclaim, reframe and realise Māori ways of knowing and being within early childhood and assessment theory and practice.